(untitled) (Fiep Bulletin - online, 2014)
The goal of the study was to evaluate and compare the short-term adaptations in body composition in two different fitness programmes a) with and b) without the electro-stimulation (EMS ) in adult women. Twenty inactive healthy women were recruited by advertisements in a fitness-studio and were selected into two groups. Group E1 (n=10, age 33.4±8.2 years, height 167.7±4.6 cm, weight 64.8±4.8 kg, BMI 23.03±1.1 kg.m-2) participated in a fitness program with the application of electro-stimulation. The group E2 (n=10, age 36.4±4.5 years, height 167.2±3.9 cm, weight 65.9±5.0 kg, BMI 23.6±1.2 kg.m-2) was involved in the same exercise program, but without the application of electro-stimulation. Both groups were involved in the training for 5 weeks, 2 times per week, and with the duration of 15 minutes per session. The anthropometric data was analyzed before and after the training period. Results of all parameters are expressed as the mean ± standard deviation (SD). Variables in the two different groups were compared by an independent Student’s t-test. The significance level was set to p ? 0.05. The results show that training with the EMS has led to a decrease in all anthropometric parameters, with the exception of BMI , as follows: Body Weight p ? 0.05, Waist Circumference p ? 0.01, Hip Circumference p ? 0.05, Waist /Hip Ratio p ? 0.05, and % Body Fat p ? 0.05. We conclude that the regular training program with the application of EMS contributes to the reduction of central obesity with weight loss, even if it is only performed 2 times per week and with the duration of 15 minutes per session. Such training could be an effective way of body forming for people with busy daily timetable.